Potential and Electric Field Characteristics of Broken Porcelain Insulator - H. Rosli; N. A. Othman; N. A. M. Jamail; M. N. Ismail (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Overhead line insulators can be damaged for various reasons during their service life. Porcelain or glass insulators once damaged can affect the reliability of power system networks. This paper presents the study of voltage and electric characteristics along the surface of a broken porcelain insulator located in a string of 10 unit insulators. Three models of broken porcelain insulators were being proposed and the analysis results on voltage and electric characteristics were individually collected. The broken porcelain insulator with the most significant effect were then being investigated in the strings of 10 unit insulators. The finite element software of Quickfield was used to analyze the voltage and electric characteristics. Form the presented results, it is proven that the single porcelain insulators with broken shed at the nearest to the electrode terminal gave the most significant effect of voltage and electric field distribution pattern along the creepage distance. However, when this type of broken insulator was included in a string of 10 unit insulators, maximum average value of voltage achieved once the broken insulator was located at the HV terminal. Meanwhile, the highest electric field strength was recorded when the broken insulator was located in the middle of the string.